Are product placements in music videos beneficial for the artists? The impact of artist–product fit on viewers' persuasion knowledge and perceived credibility of the artist - Schramm, Holger; Kraft, Jana (Frontiers in Communication, 2024)
Although product placements in music videos are ubiquitous and a common form of advertising cooperation between companies and artists, few studies have addressed the topic, especially the artists' perceptions. This experimental online study examines the effects of fit between artist and product in music videos. Results show that good artist-product-fit reduces persuasion knowledge and increases perceived credibility of the artist as well as viewers' willingness to share the video through electronic word of mouth (eWOM). These results highlight the need to understand viewers' perceptions of artists in promotional contexts to avoid dysfunctional promotional collaborations.